Segmental phonemic system of Riau Malay subdialect Kepulauan as local knowledge in Batam - Ambalegin Ambalegin; Tomi Arianto (EduLite: Journal of English Education, Literature and Culture, 2020)
Malay dialect has a specific final sound /ɑ/ as /ə/ but not all final sound /ɑ/ is pronounced as /ə/. The final sound /r/ is dropped down and the sound /u/ after the letter <r> is pronounced as /ɒ/ in some particular words. This phonemic system must be preserved and developed as a local knowledge. Modality change of consciousness happens to the Malay, and Indonesian becomes elitist and leaves the egalitarian Malay. This descriptive qualitative research concerned to the phonemic features and comprehensive picture of Malay contemporary sounds, and Malay vowels and consonants with the pertinent articulatory elements in Batam. Observation method with participatory technique involved in data collection taken from Kampong Tua Nongsa, Sanggau, Tanjung Uma, and Tanjung Riau. The theory to support the analysis was taken from Finegan and Low’s theories in term of phonological and phonetic approach and supported by Kelly, McMahon, Roach, and Yule’s theories. It is found that the letter is pronounced as /ə/ in particular place. And is pronounced as /ɒ/ in particular place. /Ɍ/ in Malay is different from /r/ in Indonesian and /ʁ/ in English as /Ɍ/ is produced by uvula. The final consonant-closed sound <k> and <l> are not sounded as they are represented by /Ɂ/. Letter <h> is not pronounced as /h/ in the final <h> consonant-closed syllable sound. /f/, /χ/, /ʃ/and /z/, all these fricative sounds do not appear in Malay. The Malay pronounced them as /p/ for /f/ in maaf, /k/ for /χ/ in ikhlas, /s/ for /ʃ/ in syukur, and /ʝ/ for /z/ in izin. Syllable sound ends with letter or <d> is not pronounced with end /b/ or /d/ but it pronounces with end /p/ or /t/ such sebab as /sebʌp/, sabtu as /sʌptʊ/, wujud as /wʊʝʊt/, and sujud as /sʊʝʊt/.